(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Hostage-taking and kidnapping have become aggressively rampant in Nigeria, particularly in the southwest, with a resultant inauguration of Western Nigeria Security Network (WNSN), codenamed ‘Amotekun’ in Southwest Nigeria. Despite the apparent success of WNSN in this region to stem these ills, it is regarded as a counter-culturist and ‘next felony,’ without considering how it has created and continue to offer another paradigm for citizens’ protection in the face of numerous security challenges. Such prevalent perceptions are fraught with claims that WNSN is a product of unconstitutionality, and ethnic mingling. Therefore, this paper beams its searchlight on the WNSN operations in Southwest Nigeria, a region that has recently become a haven for kidnappers. It examines the evolution of the WNSN as a regional security scheme to combat rising insecurity and proposes an alternative initiative to address regional security concerns. The survey evidenced that WNSN has played a key role in detecting kidnappers’ hideouts, gathering intelligence, and constantly rescuing kidnapped victims from the whims and caprices of their tormentors. It has also continued to provide robust intelligence on kidnappers to security agencies such as the Nigerian Police Force (NPF), State Security Service (SSS), and Nigeria Security and Civil Defense Corps (NSCDC), and other special forces. The paper concludes that WNSN is a positive and needful response to the long-running debate over community policing, functioning as an alternative approach to securing Nigeria against the numerous security challenges bedeviling the country.